PENGARUH PERCEIVED QUALITY, PERCEIVED VALUE, BRAND TRUST DAN BRAND IMAGE TERHADAP BRAND LOYALTY YANG DIMEDIASI OLEH CUSTOMER SATISFACTION - Dodi Ria Atmaja; Putri Lestari (POLITEKNIK LP3I JAKARTA, 2025)
Pepsodent is a toothpaste where consumers will buy toothpaste repeatedly because it has good quality at an affordable price. The aim of this research is to determine the factors that influence brand loyalty and customer satisfaction such as perceived quality, perceived value, brand identification, brand trust and brand image. This research was conducted on 145 respondents in West Jakarta who had used Pepsodent by collecting questionnaire data online. Sampling in this research was by using purposive sampling technique. With the circulation of other toothpaste brands, it is recommended that companies maintain consumer satisfaction and trust in companies that produce good quality products. The results obtained show that there is a positive and significant influence between the variables perceived quality, perceived value, brand identification, brand trust and brand image on customer satisfaction, as well as the existence of a positive and significant influence between the variables perceived quality, perceived value, brand trust and brand image on customer satisfaction. brand loyalty. Apart from that, there are several results which state that there is no positive and significant influence, namely between brand identification and brand loyalty, and customer satisfaction does not have a significant effect as a mediation between perceived value and brand loyalty, then, customer satisfaction also does not have a significant effect as a mediation between brand identification of brand loyalty